The shaping of the English landscape : an atlas of archaeology from the Bronze Age to Domesday Book - Green, Chris, (Oxford University School of Archaeology monograph., 2021)
An atlas of English archaeology covering the period from the middle Bronze Age (c. 1500 BC) to Domesday Book (AD 1086), encompassing the Bronze and Iron Ages, the Roman period, and the early medieval (Anglo-Saxon) age.